Moscow and the third World under Gorbachev / by W. Raymond Duncan and Carolyn McGiffert Ekedahi - Duncan, W Raymond (Bombay, 1990)
Since Gorbachev assumed power in 1985, So viet attitudes towards the developing world have changed dramatically. This book explores the shape and scope of the "new thinking" in Moscow's foreign policy. The authors assess Gorbachev's economic and strategic priorities in the diplomatic arena and their impact on the Third World in the context of the fixed limits to change im posed by the legacy of the past. Each regional chapter reviews past Soviet policy, exam ines the rationale for Gorbachev's present initiatives, and weighs future trends- including implications for U.S.-Soviet rela tions. Thoroughly updated through the winter of 1990, this book provides the most current analysis available of a vital and continuously evolving part of the world.
Keywords: Political Science